Behavior of Midazolam administered with three different vehicles for conscious sedation: Retrospective study - Muñoz Villanueva de Evans, Magali Natalia (2021)
When facing fear or anxiety situations some patients require treatments under conscious sedation with midazolam, which require to be mixed with a vehicle for its administration, however there is few information about how it could affect its absorption. Aim: to assess the conscious sedation level in relation to the administration of midazolam with three different vehicles. Material and Methods: observational, retrospective and comparative study of 45 conscious sedation files of which 20 met the inclusion criteria. Data was taken from the medical records and analyzed evaluating the age, gender, comparing the sedation level according to the Houpt scale and vehicle used (Paracetamol, fruit juice and brown sugar with juice in a spoon). The SPSS statistics program for the chi square test, frequency analysis, mode and mean was used to analyze de data, with a significance level of 5%. Results: Regarding the somnolence the majority of the patients showed a level 3 (drowsy). Regarding the movement there were no significant differences found according to the vehicle used. Regarding the crying the majority of the patients showed a level 3 and 4. Conclusion: The dilution of midazolam in juice showed better results regarding somnolence and crying, these differences were not statistically significant showing that the three vehicles could be useful for the administration of midazolam orally.